Anisotropic Elasticity, Spin–Orbit Coupling, and Topological Properties of ZrTe2 and NiTe2: A Comparative Study for Spintronic and Nanoscale Applications - Yasaman Fazeli; Zahra Nourbakhsh; Shahram Yalameha; Daryoosh Vashaee (Nanomaterials)
The present work investigates the interfacial and atomic layer-dependent mechanical properties, SOC-entailing phonon band structure, and comprehensive electron-topological–elastic integration of ZrTe2 and NiTe2. The anisotropy of Young’s modulus, Poisson’s ratio, and shear modulus are analyzed using density functional theory with the TB-mBJ approximation. NiTe2 has higher mechanical property values and greater anisotropy than ZrTe2. Phonon dispersion analysis with SOC effects predicts the dynamic stability of both compounds. Thus, the current research unifies electronic band structure analysis, topological characterization, and elastic property calculation to reveal how these transition metal dichalcogenides are influenced by their structural, electronic, and mechanical properties. The results obtained in this work can be used in the further development of spintronic and nanoelectronic devices.